PELATIHAN COPING RESOURCES UNTUK MENGURANGI DERAJAT STRES PADA IBU YANG BEKERJA - Natanael, Clarisa Priska; Edwina, Irene Prameswari; Cahyono, Maria Yuni Megarini (JIP (Jurnal Intervensi Psikologi), 2024)
This research aims to determine the effect of coping resources training (health and energy, problem solving skills, and positive beliefs) to reduce the degree of stress in working mothers. The design used is one group pretest and posttest design. The subjects were 11 working mothers with a maximum age of 40 years, worked a minimum of 6 hours a day, and had at least 1 child who was in kindergarten-primary school. The measuring instrument uses a stress degree measuring instrument and a copin resources measuring instrument. Data analysis used the Wilcoxon rank to compare the pretest and posttest results after being given the intervention. The results of this research show that there is a reduction in the level of stress after being given interventions that increase coping resources, problem solving skills and positive belief. The implication of this research is that training in coping resources, problem solving skills and positive belief based on an experiential learning approach can be used as a method to reduce the level of stress.